Pediatric adenotonsillectomy and postoperative hemorrhage: Demographic and geographic variation in the US. (August 2016) - Harounian, Jonathan A.; Schaefer, Eric; Schubart, Jane; Carr, Michele M.
Abstract: Objective: To examine demographic and regional variations in pediatric tonsillectomy, with or without adenoidectomy, and post-tonsillectomy hemorrhage on a national level. Methods: The MarketScan ® database was analyzed for claims made between 2008–2012 for the 30 days following tonsillectomy/adenotonsillectomy in privately insured children 1–17 years of age. Results: We analyzed 305, 860 patients with 98.6% of these tonsillectomies occurring in an ambulatory setting. Children between 3–6 years old comprised our largest group of tonsillectomies (45.1%). More tonsillectomies were done in the South (42.1%) than any other region in our sample. Patients between 11 and17 years old had the highest percentage of bleeding (4.8%). Patients between 1 and 3 years old had the lowest values. Of the 8, 518 children who presented with post-operative hemorrhage, 71.7% had only one hemorrhagic event, 28.3% had at least a second one, 6.0% had at least 3 events, and 1.3% had at least 4 events. Post-operative dehydration had a similar pattern. The South had the lowest percentage of post-tonsillectomy bleeds (2.5%) and overall ER visits (7.1%), both of which were most common in the Midwest. Gender had no significant association with incidence of tonsillectomy procedures or post-op complications. Conclusion: There are geographic and demographic variations in adenotonsillectomy and in post-operative complications for children nationally.